Limited feeding for growing-finishing swine - Koch, B.A. (Kansas Agricultural Experiment Station, 2011)
Limiting daily feed intake during the last half of the growing-finishing period is a possible way to improve carcass characteristics of market pigs. A review of limited feeding trials conducted here and elsewhere leads to these conclusions regarding limited feeding: 1. It reduces growth rate 2. Reduces excess backfat but its effect on meaty hogs is questionable 3. Requires 10 to 30 days extra feeding 4. Requires feeding in small groups 5. May or may not improve feed efficiency 6. May produce a softer carcass The study reported below compared limited feeding with full feed, and dry feeding with wet feeding.
Keywords: Swine; Daily intake; Performance; Growing-finishing swine